2020
DOI: 10.1152/ajpendo.00292.2020
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor mediates the beneficial effect of liraglutide in an acute lung injury mouse model involving the thioredoxin-interacting protein

Abstract: Repurposing clinically used drugs is among important strategies in drug discovery. Glucagon-like peptide-1 (GLP-1) and its based diabetes drugs such as Liraglutide possess a spectrum of extra-pancreatic functions, while GLP-1 receptor (GLP-1R) is most abundantly expressed in the lung. Recent studies have suggested that GLP-1-based drugs exert beneficial effects in chronic as well as acute lung injury rodent models. We show here that Liraglutide pretreatment reduced lipopolysaccharide (LPS) induced acute lung i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Thioredoxin-interacting protein (TXNIP), a critical regulator of pathological responses, is induced by various of stressors including inflammation, metabolic dysfunction, apoptosis, and lung dysfunction [ 12 , 13 , 14 ]. TXNIP has been expressed in the lungs of experimental animals exposed to lipopolysaccharide and ovalbumin (OVA), which induce increased inflammatory responses via the activation of inflammasomes [ 15 , 16 , 17 ]. In contrast, TXNIP is involved in the apoptotic response of lung tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Thioredoxin-interacting protein (TXNIP), a critical regulator of pathological responses, is induced by various of stressors including inflammation, metabolic dysfunction, apoptosis, and lung dysfunction [ 12 , 13 , 14 ]. TXNIP has been expressed in the lungs of experimental animals exposed to lipopolysaccharide and ovalbumin (OVA), which induce increased inflammatory responses via the activation of inflammasomes [ 15 , 16 , 17 ]. In contrast, TXNIP is involved in the apoptotic response of lung tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Although better glucose control from GLP1RAs may lead to low incidence of pneumonia in T2D that cannot completely explain the benefits from GLP1RAs on all the nine kinds of respiratory conditions assessed in the study. In contrast, some possible mechanisms for the benefits from GLP1RAs on relevant respiratory diseases are revealed by several small sample human studies 12,13 and animal studies 14,15 in which GLP1RAs were observed to benefit for COPD, 12,13 airway hyperresponsiveness, 14 and acute lung injury 15 via immunomodulating and antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether those extra-pancreatic functions of GLP-1 and its based drugs are mediated by certain brain-peripheral tissue axis or by a small portion of GLP-1R-producing cells scattered within each of those organs. However, we have learned for more than 25 years that lung is an extra-pancreatic organ, which exhibits the highest GLP-1R expression (102,103). Hence, great efforts have been made in clinical trials and in various lung injury models, seeking for the possibility to repurpose GLP-1-based drugs in chronic and acute lung injury treatment.…”
Section: Glp-1 Based Drugs In Lung Injury Studiesmentioning
confidence: 99%
“…In 2020, our team has directly assessed the involvement of GLP-1R in mediating effect of liraglutide treatment in LPS-induced ALI mouse model. In this study, conducted by Zhou and colleagues, liraglutide was not administrated simultaneously with LPS challenge, but as a "preventative agent" which was subcutaneously administrated 2 hours before intratracheal LPS delivery (103). In such experimental settings, we observed that liraglutide pre-treatment significantly reduced LPS-induced acute lung injury, including the reduction on lung injury score, wet/dry lung weight ratio, immune cell counts, protein concentration in bronchoalveolar lavage fluid (BALF), and cell apoptosis in the lung.…”
Section: VII Studies In Acute Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation